REALISASI KESANTUNAN TUTURAN DIREKTIF DALAM PERISTIWA TUTUR DI SMP TUNAS BANGSA GADING SERPONG - Debora, Lidya Lauren; Rosidin, Odien; Juansah, Dase Erwin (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
This study aims to analyze directive speech acts in the novel "Father" by Andrea Hirata. The method used is descriptive qualitative analysis using the theory of speech acts from Austin and Searle. Based on the results of the classification that has been carried out, there are 5 classifications, namely 5 utterances ordering, 10 utterances ordering, 10 utterances begging, 7 utterances demanding, and 8 utterances giving advice. The directive speech acts used by the characters in the novel "Ayah" by Andrea Hirata are functioned by the speaker so that the speech partner takes action according to the intent of the utterance conveyed by the speaker. The speech acts that occur in this novel are in accordance with the politeness principle where the speaker does not exceed his rights to the speech partner. The politeness in question is adjusted to the context that occurs and the social status between the speaker and the speech partner. The novel Ayah by Andrea Hirata is a mirror form of a reality of the social life of the Balitong people. Through speech acts, a person's character can be seen. The results of the study show that there are several types of directive speech acts used in the novel, such as orders, requests, invitations, and advice. In addition, directive speech acts in the novel "Father" also have a social function, namely to convey a moral message to the reader.